Financial Factors and Market Value in the Consumer Services Industry: An Empirical Study in Indonesia and Singapore - Winata, Cynthia Liusca; Arsjah, Regina Jansen (Universitas Kristen Maranatha, 2025)
Purpose – This study provides a new perspective by exploring the role of gross domestic product (GDP) as a moderating variable in the relationship between solvency, liquidity, and profitability with the market value of consumer service companies in Indonesia and Singapore. The novelty of this research lies in its holistic approach to the interaction between financial factors and macroeconomic conditions, which has rarely been examined in the context of the consumer services industry in both countries. Design/Methodology/Approach – Data was collected from consumer service companies listed on the Indonesia Stock Exchange (IDX) and Singapore Exchange (SGX) during the 2019–2023 period. This study employs panel data regression with a moderation approach, providing deeper insights into how macroeconomic variables strengthen or weaken key financial relationships. Findings – The findings indicate that solvency, profitability, and GDP have a positive impact on market value, whereas liquidity does not have a significant effect. Additionally, GDP as a moderator weakens the relationship between solvency and liquidity with market value but does not influence the relationship between profitability and market value, suggesting that profitability remains a key indicator of company value regardless of economic fluctuations.Research limitations/Implications – These results have strategic implications for investors and policymakers, highlighting that macroeconomic considerations should be integrated into financial analyses when assessing the valuation of consumer service companies. The novelty of this research offers a fresh perspective in designing investment strategies and regulatory policies, particularly in Indonesia and Singapore, which have unique and interconnected economic dynamics. Keywords: Consumer Services, GDP, Liquidity, Market Value, Profitability, and Solvency